Erythropoietin Hormone in Patients with Kidney Failure - Sahm, Sara Fawzi (American Journal of Biomedicine and Pharmacy, 2025)
Background: Studies on patients with different stages of chronic kidney diseases (CKD) have looked into the relationship between renal outcomes and iron status markers such as serum ferritin and transferrin saturation (TSAT). The relationships, meanwhile, were erratic and hotly contested. Thus, our goal was to find out if serum ferritin levels and TSAT were related to kidney outcomes in such particular populations. In this study, 109 patients were prospectively tracked after being admitted for CKD education and evaluation. Aim of the study:. Estimation of serum Erythropoietin (EPO) and Ferritin levels in those who were suffering from persistent renal failure with the third uterus compared to healthy people. Materials and methods: The study included a total of 109 samples, and 27 healthy individuals were chosen as a control group. The age range of the participants was between (40-60) years, including both genders. Specimens were obtained from outpatient clinics between January 2024 and May 2024. Results: The present study showed a decrease in Erthropotin hormone level in stage 5 kidney disease with dialysis (565.02 ±53.06c) as compared to the controls at p-value <0.05. Furthermore, this study showed an increase packed cell volume (PCV) value in stage 5 with dialysis (27.28 ± 0.91d) as compared with the control group (0.66 ± 0.89 a ) at P-value P≤0.05. In addition, a decrease in hemoglobin (Hb) levels was detected in patients with the dialysis stage 5 (8.52 ±0.32d).